COMPARISON OF DUCTUS VENOSUS DOPPLER WAVEFORM IN HYPERTENSIVE AND NON-HYPERTENSIVE PREGNANCIES (Journal of Medical & Health Sciences Review, 2025)
Objective: To rule out DV Doppler variations in HDP and assess their clinical utility.Methodology: Across-sectional study involved 110 subjects, 55 hypertensive while the other 55 were normotensive and in their second or third trimesters. The assessment was based on Doppler study of the fetal vessels in the pregnant women. The level of significance (p) was to be set at less than 0.05.Results: In hypertensive pregnancies, there was significantly higher resistance as shown by increased S/D ratio (p = 0.003), PI (p = 0.001), and RI (p = 0.037). The flow velocities associated with them were also reduced. These results were also associated with higher incidence of excessive amniotic fluid (p = 0.032).Conclusion: Ductus Venosus Doppler is a reliable method for picking up early signs of fetal distress in mothers with high blood pressure.